Zinc levels and malaria severity in children below five years in Dar-es-Salaam, Tanzania (Tanzania Medical Journal, 2009)
Introduction: Interventions which will decrease the morbidity andmortality related to Malaria are still being sought in order to improve the state of children in developing countries. Zinc is recognized to improve child health by improving immunity growth, weight and reducing episodes of infectious disease. The relation of Zinc and Malaria is still not very well understood.Objective: This cross-sectional study was undertaken to assess theZinc levels and Malaria severity in children below 5 years in Dares-Salaam, Tanzania.Methods: Fifty children each with severe malaria, non-complicatedmalaria and without malaria were studied and their plasma Zinclevels assessed at one time point on admission to study. Zinc levelswere assessed using Atomic Absorption Spectrometry. Levels ofZinc below 10mmols/dl were taken as low.Results: There was no statistical difference in their baselinecharacteristics in terms of age and gender. There was a statistically significant difference in the plasma Zinc levels between those with un-complicated and severe malaria, with an Odds ratio of 3.8 (CI 1.5-10; and p value 0.0007). The difference between those without malaria and severe malaria was slightly higher with Odds ratio of 4.1 (CI 1.6-11, and p value of 0.004).Conclusion: In conclusion, In general almost half of all children inthe study had significantly low levels of Plasma Zinc (